Occupational outcomes for Australian computing/information technology bachelor graduates and implications for the IT bachelor curriculum. Issue 3 (3rd July 2018) - Palmer, Stuart; Coldwell-Neilson, Jo; Campbell, Malcolm
ABSTRACT: In Australia, the IT workforce and employment outcomes for university IT bachelor graduates have a complex interrelationship. The likelihood of IT bachelor graduates to work in a professional IT role is infrequently discussed in the research literature. It has been suggested that "deficient" undergraduate IT curricula are one contributor to poor employment outcomes for graduates. Using the latest available Australian national census data, we present a detailed analysis of the occupational outcomes for graduates of undergraduate IT programmes, and the makeup of the IT workforce in Australia. This analysis presents important findings for those designing undergraduate IT curricula that seek to equip students to prepare for the best employment outcomes. The finding that, even immediately post-graduation, a significant proportion of Australian IT bachelor graduates do not work in IT roles, even though professional IT job roles outnumber IT bachelor graduates nearly two-to-one, has implications for undergraduate IT education.